Improving Disaster Management and Coordination in Ghana; Perspectives from Disaster Management and Response Organisations in Accra. - Sowah, H.A. (University of Ghana, 2019)
The aftermath of disasters in Ghana most especially in recent years calls for an enquiry into the nature and approach of disaster management organizations in dealing with such situations. As threats of terrorisms, flooding and earthquakes increases, there is greater demand on disaster management and response organizations to enhance their efficacy by engaging measures to reduce impact of these various types of disasters. In light of this, this study seeks to examine disaster management and coordination in Ghana. It employs a qualitative research approach with the use of both primary and secondary data sources. Officials from key disaster management organizations were purposely chosen to aid with data collection. The study revealed that, legal frameworks exist to ensure effective disaster management however implementation is a challenge. Politics, citizen attitudes, resource constraints and the challenge of coordinating actitivities of disaster management organizations continue to undermine disaster management efforts in the Ghana. The study recommends sustainable relief and reconstruction, depoliticisation of NADMO, engagement of traditional leaders and improved communication networks at ways of improving disaster management and coordination in Ghana. Keywords; Disaster, Disaster management, NADMO
MPA
Keywords: Disaster Management; NADMO; Disaster